2021
DOI: 10.1371/journal.pone.0251352
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent well-being and learning in times of COVID-19—A multi-country study of basic psychological need satisfaction, learning behavior, and the mediating roles of positive emotion and intrinsic motivation

Abstract: The sudden switch to distance education to contain the outbreak of the COVID-19 pandemic has fundamentally altered adolescents’ lives around the globe. The present research aims to identify psychological characteristics that relate to adolescents’ well-being in terms of positive emotion and intrinsic learning motivation, and key characteristics of their learning behavior in a situation of unplanned, involuntary distance education. Following Self-Determination Theory, experienced competence, autonomy, and relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 78 publications
(118 reference statements)
4
31
0
1
Order By: Relevance
“…Interestingly, however, there are also studies that do not confirm the positive effect of relatedness satisfaction on student outcomes. In their studies conducted at different school levels and across different cultural contexts, Holzer et al (2021a , b , c) found mixed results regarding the relation between relatedness and intrinsic motivation. For one, the relation between relatedness and intrinsic motivation differed across cultures.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, however, there are also studies that do not confirm the positive effect of relatedness satisfaction on student outcomes. In their studies conducted at different school levels and across different cultural contexts, Holzer et al (2021a , b , c) found mixed results regarding the relation between relatedness and intrinsic motivation. For one, the relation between relatedness and intrinsic motivation differed across cultures.…”
Section: Discussionmentioning
confidence: 97%
“…Consequently, there is no doubt that students' self-organization and self-regulation skills are considered central for distance education. In line with this assumption, many studies confirmed the strong relationship between selforganization/self-regulation and student outcomes, such as student motivation, engagement, and rated achievement in distance learning (Huber and Helm, 2020b;Grewenig et al, 2020;Blume et al, 2021;Holzer et al, 2021;Korlat et al, 2021;Pelikan et al, 2021;Steinmayr et al, 2021).…”
Section: Self-organization Skillsmentioning
confidence: 84%
“…Which aspects of teaching and learning come more to the fore in distance education, which more to the background? In early COVID-19 pandemic-related educational research, many scholars attempted to answer these questions from a theoretical (e.g., Klieme, 2020;Köller et al, 2020;Meyer, 2020;Voss and Wittwer, 2020), quantitative (e.g., Grewenig et al, 2020;Huber and Helm, 2020a;Porsch and Porsch, 2020;Holzer et al, 2021;Steinmayr et al, 2021) and qualitative perspective (e.g., Frohn, 2020;. In line with some of these early research initiatives (e.g., Wildemann and Hosenfeld, 2020;Züchner and Jäkel, 2021) we adopted the CIPO/offer-and-use logic outlined above to delineate and identify relevant predictors of student learning during the pandemic.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Also, all domains were related in a reciprocal way, that is, connectedness fostered well-being which in turn was related to increases in connectedness ( Jose et al, 2012 ). Recent studies on distance learning under COVID-19 restrictions also highlighted the importance of perceived relatedness for well-being, such as the study by Holzer et al (2021) which found a significant positive association of perceived relatedness with positive emotions (and learning-related outcomes) among more than 25,000 adolescents from eight different countries.…”
Section: Theorymentioning
confidence: 99%